Dual targeted therapy in patients with psoriatic arthritis and spondyloarthritis: a real-world multicenter experience from Spain - Valero-Martínez, Cristina; Urgelles, Judit Font; Sallés, Meritxell; Joven-Ibáñez, Beatriz E.; de Juanes, Alexia; Ramírez, Julio; Juanola, Xavier; Almodóvar, Raquel; Laiz, Ana; Moreno, Mireia; Pujol, Manel; Beltrán, Emma; et al. (Frontiers in Immunology, 2023)
Dual biological or synthetic targeted therapy (DTT) has emerged as a promising approach in patients with refractory spondyloarthritis (SpA) or psoriatic arthritis (PsA) and extra-musculoskeletal manifestations of both diseases, but its effectiveness/safety ratio still remains unclear. This is a retrospective, real-world multicenter study in refractory SpA and PsA patients with simultaneous use of two biological or synthetic targeted agents. Effectiveness was assessed using Ankylosing Spondylitis Disease Activity Score with C-reactive protein (ASDAS-CRP) and Disease Activity in Psoriatic Arthritis (DAPSA) Score. We identified 39 different DTT combinations in 36 patients (22 SpA; 14 PsA), 25 of them with concomitant inflammatory bowel disease. The most commonly used combinations were TNF inhibitor plus antagonist of the IL12/23 pathway, followed by TNF inhibitor plus IL-17 antagonist. During a median DTT exposure of 14.86 months (IQR 8-20.2), DTT retention rate was 69.4% (n=25/36; 19 SpA, 6 PsA). Major clinical improvement (change in ASDAS-CRP > 2 or improvement > 85% in DAPSA) was achieved in 69.4% of patients (n=25/36 therapeutical combinations; 17/21 SpA, 8/15 PsA), with a 58.3% (n=21/36 combinations; 15/20 SpA, 6/13 PsA) low-activity/remission rate. Of the patients who were receiving glucocorticoids, 55% managed to withdraw them during follow-up. Interestingly, only four serious adverse events in three patients were observed, leading to DTT discontinuation.